Internalisasi Praktik Beragama: Kontribusi Madrasah Pada Pembentukan Karakter Pemuda Indonesia - Diana Rohali; Afifah Afifah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
This research aim to describe: 1. How the process of internalizing religious values through exemplary and habituation method in Ad-dzikir Pragaan elementary school. 2. What are supporting and inhibiting factors of internalizing religious values through exemplary and habituation method in Ad-dzikir Pragaan elementary school. This research used qualitative approach, informan of this research are principal, master of classes, and students of Ad-Dzikir. Data collection technique used are observation, interview and documentation. Data analysis used are data reduction, data presentation and conclusion. The result showed that the process of internalizing religious values through exemplary method in Ad-dzikir Pragaan elementary school are ilahiyah values, insaniyah values, akhlaq values. The teacher behavior as role models are: discipline, on time both in school or class, appreciated students tasks, became imam when dhuhur prayer, assertive, gave advice and motivation. The process of internalizing religious values through habituation method in Ad-dzikir Pragaan elementary school are time, condition and program habituation.